1993
DOI: 10.7326/0003-4819-119-1-199307010-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Teaching and Practice of Cardiac Auscultation during Internal Medicine and Cardiology Training: A Nationwide Survey

Abstract: A low emphasis on cardiac auscultation appears to have affected the proficiency of medical trainees. Our study raises concern about the future of this time-honored art and, possibly, other bedside diagnostic skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
2
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(164 citation statements)
references
References 0 publications
6
152
2
4
Order By: Relevance
“…The 12 findings were selected based on results of a previously published national survey of internal medicine and family residency program directors. 21 The intervention included a computer based, interactive self study tutorial (UMedic) 22 developed at the University of Miami which features didactic instruction, deliberate practice, and self assessment. Students accessed this program at Northwestern's Clinical Education Center and used headphones to listen to the heart sounds.…”
Section: Educational Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 12 findings were selected based on results of a previously published national survey of internal medicine and family residency program directors. 21 The intervention included a computer based, interactive self study tutorial (UMedic) 22 developed at the University of Miami which features didactic instruction, deliberate practice, and self assessment. Students accessed this program at Northwestern's Clinical Education Center and used headphones to listen to the heart sounds.…”
Section: Educational Interventionmentioning
confidence: 99%
“…However, research has shown that clinical experience does not correlate with skill in this core competency. [1][2][3][4] One study showed that medical students identified only 20% of 12 cardiac events correctly and the accuracy of residents was no better at 19%. 2 Another investigation showed that except for cardiology fellows, there was no improvement in auscultation skills after the third-year of medical school among medical students, residents and faculty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relative auscultation skill for primary care providers and noncardiology specialists is unknown, studies comparing medical students and internal medicine residents found no improvement in auscultation skill following the third year of medical school. 23,24 Thus, we believe the accuracy of auscultation we observed is likely to be typical of community primary care practice.…”
Section: Limitationsmentioning
confidence: 68%
“…Despite decades of pleas to reprioritize PE, 9 GME training in aspects of PE is underemphasized whenever formally assessed. [10][11][12][13][14] Furthermore, residents' examination skills in many contexts, including cardiovascular, pulmonary, breast, rheumatologic, and genitourinary systems, among others, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] are suboptimal.…”
Section: Introductionmentioning
confidence: 99%